Factors related to mortality in patients with acute respiratory distress syndrome (ARDS) in a lower middle-income country: A retrospective observational study - Co Xuan Dao; Chinh Quoc Luong; Toshie Manabe; My Ha Nguyen; Dung Thi Pham; Quynh Thi Pham; Tai Thien Vu; Hau Thi Truong; Dai Quoc Khuong; Hien Duy Dang; Tuan Anh Nguyen; Thach The Pham; et al. (PLoS ONE, 2025)
Background Acute respiratory distress syndrome (ARDS) is associated with a high mortality rate, particularly in low- and middle-income countries, where the quality of pre-hospital or inter-hospital care can significantly impact patient outcomes. This study aimed to investigate mortality rates and associated factors among ARDS patients in Vietnam. Methods This retrospective observational study included adult ARDS patients admitted to a central hospital in Vietnam from August 2015 to August 2023. Data was collected on inter-hospital care, patient characteristics, management, and outcomes; comparisons were made between survivors and non-survivors, and logistic regression analyses were performed to identify factors independently associated with hospital mortality. Results Of 353 patients, 68.0% were male, the median age was 55.0 years (Q1-Q3: 39.0–66.0), and 61.5% died in the hospital. The majority of patients (89.5%; 316/353) were transferred from local hospitals, and 80.6% (253/314) had received non-invasive or invasive mechanical ventilation (MV) at the referring hospital. During transportation, 60.1% (116/193) had an endotracheal tube (ET) in place, and 25.6% (41/160) received non-invasive or invasive MV. Upon admission, the mean PaO 2 /FiO 2 ratio was 110.04 mmHg (SD: 57.72), and the median Sequential Organ Failure Assessment (SOFA) score was 10.0 (Q1-Q3: 7.0–12.0). Most patients (95.7%; 315/329) received invasive MV on the first day of admission, and 36.7% (73/199) underwent cytokine adsorption during their hospital stay. The univariable logistic regression identified several factors significantly associated with hospital mortality, including age (OR: 1.027; 95% CI: 1.013–1.040; p < 0.001), PaO 2 /FiO 2 ratio (OR: 0.993; 95% CI: 0.989–0.996; p < 0.001), SOFA Score (OR: 1.168; 95% CI: 1.093–1.250; p < 0.001), and septic shock (OR: 2.077; 95% CI: 1.338–3.226; p = 0.001). However, in multivariable analysis, only the use of an ET during transportation remained independently associated with reduced hospital mortality (adjusted OR: 0.070; 95% CI: 0.005–0.937; p = 0.045). Conclusions This study investigated a selected cohort of patients and underscored the vital role of pre-hospital and inter-hospital care in ARDS outcomes in Vietnam. Most patients were transferred from local hospitals, with limited application of essential transport interventions such as ET and MV. Notably, the use of an ET during transfer was independently associated with reduced hospital mortality. To improve survival, healthcare strategies should prioritize strengthening inter-hospital transfer protocols, ensuring timely initiation of respiratory support, and expanding access to critical care resources across all levels of the healthcare system.